Resistance to anti-EGFR therapies in metastatic colorectal cancer: underlying mechanisms and reversal strategies - Zhou, Jing; Ji, Qing; Li, Qi (Journal of experimental & clinical cancer research, 2021)
Cetuximab and panitumumab are monoclonal antibodies (mAbs) against epidermal growth factor receptor (EGFR) that are effective agents for metastatic colorectal cancer (mCRC). Cetuximab can prolong survival by 8.2 months in RAS wild-type (WT) mCRC patients. Unfortunately, resistance to targeted therapy impairs clinical use and efficiency. The mechanisms of resistance refer to intrinsic and extrinsic alterations of tumours. Multiple therapeutic strategies have been investigated extensively to overcome resistance to anti-EGFR mAbs. The intrinsic mechanisms include EGFR ligand overexpression, EGFR alteration, RAS/RAF/PI3K gene mutations, ERBB2/MET/IGF-1R activation, metabolic remodelling, microsatellite instability and autophagy. For intrinsic mechanisms, therapies mainly cover the following: new EGFR-targeted inhibitors, a combination of multitargeted inhibitors, and metabolic regulators. In addition, new cytotoxic drugs and small molecule compounds increase the efficiency of cetuximab. Extrinsic alterations mainly disrupt the tumour microenvironment, specifically immune cells, cancer-associated fibroblasts (CAFs) and angiogenesis. The directions include the modification or activation of immune cells and suppression of CAFs and anti-VEGFR agents. In this review, we focus on the mechanisms of resistance to anti-EGFR monoclonal antibodies (anti-EGFR mAbs) and discuss diverse approaches to reverse resistance to this therapy in hopes of identifying more mCRC treatment possibilities.